2012
DOI: 10.1007/s00221-012-3134-4
|View full text |Cite
|
Sign up to set email alerts
|

The spatial range of contour integration deficits in schizophrenia

Abstract: Contour integration (CI) refers to the process that represents spatially separated elements as a unified edge or closed shape. Schizophrenia is a psychiatric disorder characterized by symptoms such as hallucinations, delusions, disorganized thinking, inappropriate affect, and social withdrawal. Persons with schizophrenia are impaired at CI, but the specific mechanisms underlying the deficit are still not clear. Here, we explored the hypothesis that poor patient performance owes to reduced feedback or impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
10
13
0
Order By: Relevance
“…We also found abnormal contextual modulation among patients, with parallel flankers causing less of a performance decrement (relative to random) for patients than for controls. One explanation for our pattern of results is that schizophrenia leads to an overall impairment in contour integration, in agreement with previous reports [813,3539]. This is supported by the group difference observed in contour detection thresholds (but no significant group by condition interaction), with patients showing poorest group mean performance in all three flanker conditions.…”
Section: Discussionsupporting
confidence: 93%
“…We also found abnormal contextual modulation among patients, with parallel flankers causing less of a performance decrement (relative to random) for patients than for controls. One explanation for our pattern of results is that schizophrenia leads to an overall impairment in contour integration, in agreement with previous reports [813,3539]. This is supported by the group difference observed in contour detection thresholds (but no significant group by condition interaction), with patients showing poorest group mean performance in all three flanker conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Behavioral data were not collected from 1 patient and 2 controls in the low-jitter condition and 2 patients and 2 controls in the high-jitter condition. Effect sizes for ANOVAs are reported as partial eta squared (η 2 p ) to be consistent with past studies of contour integration (Keane et al, 2012; Silverstein et al, 2012). …”
Section: Methodssupporting
confidence: 81%
“…With the JOVI and other similar CI tasks, studies have shown that people with schizophrenia are less able to detect and make shape judgments about fragmented contours when compared to various healthy and psychiatric control groups (Butler et al, 2013; Feigenson, Keane, Roche, & Silverstein, 2014; Keane, Erlikhman, Kastner, Paterno, & Silverstein, 2014; Keane et al, 2012; Kozma-Weibe et al, 2006; Schallmo, Sponheim, & Olman, 2013a, 2013b; Schenkel, Spaulding, DiLillo, & Silverstein, 2005; Schenkel, Spaulding, & Silverstein, 2005; Silverstein et al, 2009; Silverstein et al, 2006; Silverstein et al, 2012; Silverstein, Kovacs, Corry, & Valone, 2000; Uhlhaas, Phillips, Schenkel, & Silverstein, 2006; Uhlhaas, Phillips, & Silverstein, 2005). Past CI studies in schizophrenia have also demonstrated that, while performance does not vary from the acute to stabilization phases of illness in briefly hospitalized (i.e., ~2 weeks) patients (Feigenson et al, 2014), it becomes worse with longer illness chronicity and a lower level of functioning (Schenkel, Spaulding, & Silverstein, 2005; Silverstein et al, 2006; Uhlhaas et al, 2005).…”
Section: 0 Introductionmentioning
confidence: 99%